The Indian oilseeds scenario : Challenges and opportunities: THE INDIAN OILSEEDS SCENARIO : CHALLENGES AND OPPORTUNITIES - R S PARODA (Journal of Oilseeds Research, 2013)
Vegetable oils are critical for the nutrition security of our people in India. Through technological means such as refining, bleaching and deodorisation, newer oils like cotton seed, sunflower, palm oil, soybean and rice bran have become popular in recent times. India occupies a prominent place in global oilseeds scenario with 12-15% of area, 6-7% of vegetable oil production, and 9-10% of the total edible oil consumption and 13.6% of vegetable oil imports. The oilseeds sector has remained vibrant globally with 4.1% growth per annumin the last three decades. In India, oilseeds account for nearly 3% of the gross domestic product and 5.98% of the value of all agricultural products. India hasrich diversity of annual oilseed crops on account of diverse agro-ecological conditions. Nine annual oilseeds, which include seven edible oilseeds, viz., groundnut, rapeseedmustard, soybean, sunflower, sesame, safflower and niger and two non-edible crops, viz., castor and linseed are grown in the country. Despite having the largest area under oilseeds in the world (26.77 mha), India currently imports about 50% of total oil requirement at a huge cost of ` 56,000 crores (2011-12). The proportion of import has increased from a meagre 3% in 1970-71 to almost 56% in 2012-13.